Thermo-microstratigraphy of shells reveals invisible fire use and possible cooking in the archaeological record - Simões, Carlos D.; Aldeias, Vera (Frontiers in Earth Science, 2022)
The archaeological visibility of hearths related to shellfish cooking methods is limited, particularly in pre-ceramic shell midden contexts. Important evidence for use of fire is the thermal alteration of components, namely the identification of burnt shells. Mollusk shells that mineralize as aragonite are particularly indicative of burning due to the conversion of aragonite to calcite through recrystallization at known temperature thresholds. However, roasting temperatures needed to open bivalves, do not necessarily cause thermal alterations in the cooked shell. This complicates the significance of shell mineralogy by itself to recognize cooking, and discerning pre-depositional from in situ heating. To distinguish between cooking and burning, we combine micromorphological analyses with microscopic Fourier transformed infrared spectroscopy to investigate mineralogical thermo- alterations alongside microstratigraphic formation studies. Experimentally heated specimens of Cerastoserma edule and Scrobicularia plana are used to identify the temperature thresholds of biogenic calcium carbonate phase alteration at the micro-scale. These results are then used to interpret mineral alterations in deposits from two Mesolithic shell midden contexts from Portugal. Micro-stratigraphically controlled mineralogy proved to be particularly useful to distinguish between pre-depositional heating from in situ heating, configuring a novel methodology for recognition of traces of cooking shellfish versus traces of fire used for other purposes. Mapping the mineral phase conversion at a micro stratigraphic scale also allow to identify instances of in situ fire events that were invisible macroscopically. This combined microstratigraphic and mineralogical methodology considerably increases our capacity of deciphering intricate shell midden stratigraphy and occupational events.